PERAN SELF-EFFICACY DALAM MEMEDIASI PENGARUH PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA UKM MANUFAKTUR DI BALI - Putu Pradiva Putra Salain; I Gede Rihayana; I Nengah Suardhika (Universitas Mahendradatta, 2026)
This study aims to analyze the role of self-efficacy in mediating the influence of job training on employee performance in manufacturing SMEs in Denpasar City, Bali. The study used a quantitative approach with a saturated sampling technique on 32 employees. Data were collected through questionnaires and analyzed using Partial Least Square (PLS) with SmartPLS 4.0. The results showed that job training had a positive and significant effect on employee performance and self-efficacy. Self-efficacy was also proven to have a positive and significant effect on employee performance. In addition, self-efficacy was able to mediate the effect of job training on employee performance. These findings indicate that improving the quality of job training can strengthen employee self-confidence and improve their performance. Therefore, manufacturing SMEs need to develop structured and sustainable training programs to support productivity and business competitiveness in the digital era.